2018
DOI: 10.1038/s41467-018-02895-9
|View full text |Cite|
|
Sign up to set email alerts
|

Liquid crystal elastomer coatings with programmed response of surface profile

Abstract: Stimuli-responsive liquid crystal elastomers with molecular orientation coupled to rubber-like elasticity show a great potential as elements in soft robotics, sensing, and transport systems. The orientational order defines their mechanical response to external stimuli, such as thermally activated muscle-like contraction. Here we demonstrate a dynamic thermal control of the surface topography of an elastomer prepared as a coating with a pattern of in-plane molecular orientation. The inscribed pattern determines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 40 publications
(54 reference statements)
1
125
2
Order By: Relevance
“…Reducing the order parameter at elevated temperatures results in forming protrusions in the chiral nematic region with a height of a hundred nanometers. Babakhanova et al have shown similar effects with an LCN coating on glass that exhibits a well‐controlled director pattern of radially aligned elements containing a regular array of +1 and −1 defects. Changing the scalar order parameter by heating to the rubbery state above the glass transition, the LCN coating forms hills and valleys of tens of nanometers exactly at the locations of the defects where the directors coincide.…”
Section: Light‐responsive Liquid Crystal Networkmentioning
confidence: 84%
“…Reducing the order parameter at elevated temperatures results in forming protrusions in the chiral nematic region with a height of a hundred nanometers. Babakhanova et al have shown similar effects with an LCN coating on glass that exhibits a well‐controlled director pattern of radially aligned elements containing a regular array of +1 and −1 defects. Changing the scalar order parameter by heating to the rubbery state above the glass transition, the LCN coating forms hills and valleys of tens of nanometers exactly at the locations of the defects where the directors coincide.…”
Section: Light‐responsive Liquid Crystal Networkmentioning
confidence: 84%
“…Here, we used the simplest case, where the LC director is uniform. However, using photoalignment approaches, for instance, allow one to generate any desired director field orientations (Babakhanova et al, 2018;Guo et al, 2016;Ware, McConney, Wie, Tondiglia, & White, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Inkjet printing was also applied to prepare a microactuator showing complicated motion mimicking natural cilia . Moreover, surface properties of CLCP films, such as adhesion and friction, were controlled through switching of surface topography at the microscopic scale …”
Section: Structures Of Photomobile Polymer Materials From Nano To Macromentioning
confidence: 99%